MARSTRUCT benchmark study on nonlinear FE simulation of an experiment of an indenter impact with a ship side-shell structure. (May 2018) - Ringsberg, Jonas W.; Amdahl, Jörgen; Chen, Bai Qiao; Cho, Sang-Rai; Ehlers, Sören; Hu, Zhiqiang; Kubiczek, Jan M.; Kõrgesaar, Mihkel; Liu, Bin; Marinatos, Janis N.; Niklas, Karol; Parunov, Joško; et al.
Abstract: This paper presents a benchmark study on collision simulations that was initiated by the MARSTRUCT Virtual Institute. The objective was to compare assumptions, finite element models, modelling techniques and experiences between established researchers within the field. Fifteen research groups world-wide participated in the study. An experiment involving a rigid indenter penetrating a ship-like side structure was used as the case study. A description of how the experiment was performed, the geometry model of it, and material properties were distributed to the participants prior to their simulations. The paper presents the results obtained from the fifteen FE simulations and the experiment. It presents a comparison of, among other factors, the reaction force versus the indenter displacement, internal energy absorbed by the structure versus the indenter displacement, and analyses of the participants' ability to predict failure modes and events that were observed in the experiment. The outcome of the study is a discussion and recommendations regarding mesh size, failure criteria and damage models, interpretation of material data and how they are used in a constitutive material model, and finally, uncertainties in general. Highlights: Benchmark study on nonlinear FE simulation of an experiment of an indenter impact with a ship side-shell structure. Participants from fifteen research groups world-wide. Recommendations regarding mesh element size, failure criterion and damage models. Recommendations regarding interpretation of material data and how they are used in a constitutive material model.